Multicultural counseling applications for improved mental healthcare services - Jegathesan, Anasuya Jegathevi, 1974-; Abdullah, Siti Salina, 1978- (Medical Information Science Reference, 2019)
"This book provides practical applications and techniques alongside relevant theoretical frameworks applied by practitioners in the areas of mental health. It also provides insights to cultural and religious groups seeking to improve mental wellness for their adherents"--Provided by publisher